2015
DOI: 10.1016/j.annepidem.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Response of biomarkers of inflammation and coagulation to short-term changes in central site, local, and predicted particle number concentrations

Abstract: Purpose-Previous studies have reported acute (hours-28 days) associations between ambient ultrafine particles (UFP; diameter <0.1) and biomarkers of cardiovascular health using central site data. We evaluated particle number concentration (a proxy measure for UFP) measured at a central site, a local near-highway site and predicted residential concentrations with response of biomarkers of inflammation and coagulation in a near-highway population.Methods-Participants provided two blood samples for analysis of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In the absence of a sufficient washout period, effects could carry over into the subsequent sham period diluting the apparent impact on biomarkers. Observational panel studies suggest that hsCRP and IL-6 could have maximal changes in response to UFP at three to four weeks [34, 35]. We accounted for carryover effects in our statistical analysis, but it would have been preferable to eliminate them from affecting biomarker data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of a sufficient washout period, effects could carry over into the subsequent sham period diluting the apparent impact on biomarkers. Observational panel studies suggest that hsCRP and IL-6 could have maximal changes in response to UFP at three to four weeks [34, 35]. We accounted for carryover effects in our statistical analysis, but it would have been preferable to eliminate them from affecting biomarker data.…”
Section: Discussionmentioning
confidence: 99%
“…In our review of the literature, we found that only one [36] out of five [16, 17, 29, 37] recent HEPA intervention studies for CV outcomes had a washout period. Further, all but two of these studies had intervention periods that were shorter than we suspect is necessary (three weeks or more) based on observational studies [34, 35, 38, 39]. Given the logistical challenge of adding long washout periods to randomized crossover trials, it is worth considering standard randomized controlled trials, as have been used in some HEPA intervention studies for asthma [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on the health effects of UFP is growing rapidly [17]. Acute exposure to ambient UFP has been associated with decreased lung function, decreased heart rate variability, increased inflammation and coagulation in the lungs and peripheral blood, and risk of myocardial infarctions [1824].…”
Section: Introductionmentioning
confidence: 99%
“…Acute exposure to ambient UFP has been associated with decreased lung function, decreased heart rate variability, increased inflammation and coagulation in the lungs and peripheral blood, and risk of myocardial infarctions [1824]. Chronic ambient exposure to UFP has been associated with increased risks of overall and cardiovascular mortality and increased systemic inflammation and oxidative stress [17, 25, 26]. …”
Section: Introductionmentioning
confidence: 99%